Evaluation of Antioxidant Activity of Ethanol Extract from Phyllospongia lamellosa Obtained in Parentek Beach, Minahasa Regency - Karunia Ritje Virginia Rintjap; Adithya Yudistira; Yuanita Amalia Hariyanto (PHARMACON, 2024)
Sponges are one of the components of coral reef biota that are quite widespread. Almost 75% of the sponge species found in the waters are classes of Demospongiae. Asymmetrical in shape, demospongiae grow in various sizes from small to more than 2 meters. This study aims to determine the antioxidant activity of ethanol extract of Phyllospongia lamellosa obtained using DPPH method. The results of data analysis of % inhibition values are 20 ppm concentration (41.80%), 40 ppm concentration (43.78%), 60 ppm concentration (46.65%), 80 ppm concentration (47.25%), 100 ppm concentration (48.42%). This shows that the Phyllospongia lamellosa sponge sample obtained from Parentek Beach, Minahasa Regency has antioxidant effectiveness but is not active because the highest percent inhibition value at a concentration of 100 ppm is only 48.42%.